Synthetic peptides from conserved regions of the Plasmodium falciparum early transcribed membrane and ring exported proteins bind specifically to red blood cell proteins (2009)
Severe malaria pathology is directly associated with cytoadherence of infected red blood cells (iRBCs) to healthy RBCs and/or endothelial cells occurring during the intraerythrocytic development of Plasmodium falciparum. We synthesized, as 20-mer long peptides, the members of the ring exported (REX) protein family encoded in chromosome 9, as well as the early transcribed membrane proteins (E-TRAMP) 10.2 and 4, to identify specific RBC binding regions in these proteins. Twelve binding peptides were identified (designated as HABPs): three were identified in REX1, two in REX2, one in REX3, two in REX4 and four in E-TRAMP 10.2. The majority of these HABPs was conserved among different P. falciparum strains, according to sequence analysis. No HABPs were found in E-TRAMP 4. Bindings of HABPs were saturable and sensitive to the enzymatic treatment of RBCs and HABPs had different structural features, according to circular dichroism studies. Our results suggest that the REX and E-TRAMP families participate in relevant interactions with RBC membrane proteins, which highlight these proteins as potential targets for the development of fully effective immunoprophylactic methods. © 2009 Elsevier Ltd. All rights reserved.